Long-COVID, neurological and cardiovascular disorders - Saienko, Oleksandr; Chemych, Mykola; Svitailo, Vladyslav (Journal of Education, Health and Sport, 2023)
Introduction. After the disease COVID-19 caused by the SARS-CoV-2 virus, many people recover completely, but others have symptoms that persist for weeks, months or even years after the illness, with the number of patients who are worried about the signs of Long-COVID constantly growing. The aim. Study of the features of the epidemiological and clinical course, pathophysiological mechanisms of long-COVID development, based on the study and analysis of modern scientific data and the establishment of causal relationships of damage to the nervous and cardiovascular systems. Materials and methods. The electronic databases Scopus, PubMed, Web of Science, using modern technologies (Obsidian), key terms and words related to Long COVID, distant neurological and cardio-vascular complications have been studied and analyzed. Conclusions. "Long COVID" is conceptualized as a multiorgan disorder with a wide range of clinical signs that may indicate primarily damage to the nervous and cardiovascular systems. Central or peripheral nervous system lesions occur in more than one-third of patients. Cardiovascular complications, including stroke, are the predominant causes of death of people with "long COVID" (40 %). The most frequent neurological signs of "Long COVID" (>70 %) are fatigue, headache, sleep disorders, emotional disorders and sensorimotor disorders. The processes of neuroinflammatory and oxidative stress predominate in the spread of neurological consequences of "Long COVID".